PENGARUH MEDIA BIG BOOK UNTUK MENINGKATKAN HASIL BELAJAR PADA MATERI CERITA WAYANG KELAS II SDN 3 KALIAMAN - Hana Laila Safra; Wiranti , Dwiana Asih (Jurnal Riset Madrasah Ibtidaiyah (JURMIA), 2025)
The purpose of this research is to analyze the impact of Big Book media utilization on the improvement of Javanese language learning outcomes, especially Wayang Story material, for second grade students at SDN 3 Kaliaman. The type of research applied is quantitative with analysis methods including validity, reliability, data normality, and t-test hypothesis testing. Data were collected through documentation, observation, and questionnaire techniques. A total of 18 grade II students became the subject of this research, with the application of pre-experimental design model One Group Pretest-Posttest Design. The instrument used was a multiple choice question of 20 items. Data processing was carried out using the IBM SPSS Statistics version 25 application through the t test. The research findings show a significance value (2-tailed) of 0.000, which is smaller than 0.05 (0.000 < 0.05), with α = 0.05. This causes the null hypothesis (Ho) to be rejected and the alternative hypothesis (Ha) to be accepted, which indicates that the use of Big Book media has a significant impact on the learning outcomes of grade II students in learning Javanese. The increase can be seen from the Posttest score which is higher than the Pretest score. Thus, it can be concluded that the utilization of Big Book media significantly affects the learning outcomes of grade II students at SDN 3 Kaliaman.